Dietary Patterns and Determinants of Pregnant and Lactating Women From Marginalized Communities in India: A Community-Based Cross-Sectional Study - Sharma, Shantanu; Akhtar, Faiyaz; Kumar Singh, Rajesh; Mehra, Sunil (Frontiers in Nutrition, 2020)
Objective: Dietary pattern analysis has emerged as a balanced and realistic approach that reflects how the food is consumed in real life. However, previous studies have overlooked the two important phases in women’s life, pregnancy, and lactation. We aimed to explore dietary patterns and their determinants among pregnant and lactating women from marginalized families in rural areas and urban slums of India. Methods: It was a community-based cross-sectional study conducted across four districts of India, one from each region (North, West, East, and South). We used a structured questionnaire to collect data on socio-demographic characteristics and access to nutrition services. The dietary data were collected using a qualitative food frequency questionnaire having 204 food items, which were clubbed into 16 major food groups. The principal component analysis method was employed to identify dietary patterns (prefixed at 4). We used multinomial logistic regression to explore associations of socio-demographic and access to nutrition services’ variables with identified dietary patterns. Results: The data of 476 pregnant and 446 lactating women were assessed. Four patterns explained for 54% of the variation in their food intake. The patterns identified were low-mixed vegetarian (19%), non-vegetarian (15%), high-mixed vegetarian (11%), and calorie-rich (9%). The low-mixed diet was rich in rice, roots and tubers, green leafy vegetables, and other vegetables. The non-vegetarian diet was characterized by high loadings for nuts or seeds, chicken, meat or fish, eggs, beverages (milk-based), and snacks. The high-mixed diet was rich in cereals other than rice and wheat, pulses, and fruits. The calorie-rich diet had high factor loadings for wheat, butter and oil, sweets, and milk and milk products. Hindus and women who lived in rural areas had higher odds of consuming a low-mixed diet and lower odds of a high-mixed diet. Working women and those who received nutrition advice during pregnancy or lactation had 2-3 times higher odds of consuming a high-mixed diet. Conclusions: A high prevalence of a low-mixed vegetarian diet among women can have adverse pregnancy and birth outcomes. Healthy dietary patterns during pregnancy and lactation are required to meet the increased nutrient requirements for improved maternal and child health.